CHARACTERISTICS OF INFLUENZA INFECTION IN 2017 AND CURRENT PRACTICE: A RETROSPECTIVE STUDY AT A COLLEGE HOSPITAL IN JEDDAH: Pharmaceutical Science-Medicine - SULTAN, INTESSAR; MOAMENA, MONTASIR; DEGNAH, AMMAR; ALHARBI, BANDAR; ALHABI, HATIM; ALSAADI, ASSAD (International Journal of Life Science and Pharma Research, 2019)
Saudi Arabia has recentlystarted a surveillance process for seasonal influenza outbreaks. Special interest should be given to the influenza-associated severe acute respiratory infection (SARI) to describe the epidemiological and clinical characteristics and current practice of influenza-associated SARI in 2017. A retrospective observational study was conducted at IbnSina National College Hospital in Jeddah in 2018. Review of medical records was done using checklists for in-patients who did rapid influenza diagnostic tests during 2017 using nasopharyngeal swabs and for whom coronavirus RT-PCR test was also performed by the “Saudi National Health Laboratory”. Data collection included time of admission, demographic, clinical, and laboratory data, treatment, and outcome. Among 300 in-patients with fever, 31.3% had SARI due to influenza A rather than B but not H1N1 or MERS-CoV infection. SARI cases clustered during July and September (‘Ramadan’ and ‘Hajj’ periods). The risk of flu-related complications was high (45.7%) and included mostly children < 5 and presented mainly with pneumonia (21.3%). The main presentations were fever (83%), flu-like symptoms (41.9%), nonproductive cough (33%), dyspnea (25%), vomiting (14.9%), and abdominal pain (8.5%). Patients had lymphocytosis (27.7%) and neutropenia (20.2%).All received antiviral oseltamivir (16% received it late, 3.4% did not continue after discharge) and 90.4% received empirical antibiotics. All recovered completely with no ICU admission. Seasonal influenza A-associated SARI in 2017 in our hospital coincided with ‘Ramadan’ and ‘Hajj’ periods, presented with typical symptoms, and had a high risk of complications, especially pneumonia. It was amenable to antiviral therapy with a favorable outcome. Most patients received empirical antibiotics and a few did not receive proper antiviral therapy. Physicians should consider early antiviral treatment in patients with suspected SARI during influenza seasons. There is a need for national recommendations to guide antibiotic strategies and regimens in influenza-associated SARI.